EVALUATION OF GENETIC DIVERSITY OF SOYBEANACCESSIONS USING SSR MARKERS - Amangeldiyeva, A.A.; Yerzhebayeva , R.S.; Didorenko , S.V. (Eurasian Journal of Applied Biotechnology, 2025)
Soybean (Glycine max L.) is an important legume crop used to meet the protein and oil demands of many populations worldwide. Assessing the genetic diversity of soybean accessions is crucial for expanding the genetic base and improving the efficiency of breeding programs. The aim of this study was to evaluate the genetic diversity of 188 soybean accessions using 15 polymorphic SSR markers to determine the degree of their genetic differentiation and their potential for use in breeding. As a result of the study, a total of 55 alleles were identified, with an average of 2.68 alleles per locus. The polymorphic information content (PIC) ranged from 0.35 (Satt385) to 0.74 (Satt409), with an average of 0.61. The expected heterozygosity (He) ranged from 0.35 (Satt385) to 0.74 (Satt409), with an average value of 0.60. Furthermore, a phylogenetic Neighbor-Joining (NJ) dendrogram based on the binary allele data revealed three main clusters, each of which was divided into two subclusters. In addition, the analysis of molecular genetic data using the UPGMA method allowed the identification of two and one main clusters at different levels of genetic distance (0.21; 0.22). The obtained clusters reflect various relationships between local and foreign genotypes, indicating both the preservation of the local gene pool and its expansion through the inclusion of foreign cultivars. The information on genetic diversity among soybean genotypes obtained in this study will assist breeders in selecting parental lines for future breeding programs.